2006
DOI: 10.1073/pnas.0604053103
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of receptor editing at the λ locus: Multireactivity and light chain secretion

Abstract: To investigate the manner in which B cells with light (L) chains undergo receptor editing, we have studied hybridoma panels from 56R͞-deleted (kdel) mice. 56R͞kdel mice only produce four L chains (1, 2, 3, and X). They also have a simplified heavy (H) chain repertoire: All B cells start out with a 56R anti-DNA H chain. A few frankly autoreactive 56R 1 cells appear to escape into the periphery, but the majority of the peripheral B cell repertoire in 56R͞kdel is made up of B cells expressing the 56R H chain with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
2
30
1
Order By: Relevance
“…9A. Our binding results are consistent with those of Doyle et al (60) who also found 56RV x-expressing B cell hybridomas to produce Ab with specificity for dsDNA, but they differ from those of earlier reports showing the V 21D and V x editors to inhibit completely the binding of 56R to dsDNA (4,18,50). The basis for the difference is unclear.…”
Section: Igm Molecules Secreted By 56rv 21d-and 56rv X-expressing Hybsupporting
confidence: 40%
“…9A. Our binding results are consistent with those of Doyle et al (60) who also found 56RV x-expressing B cell hybridomas to produce Ab with specificity for dsDNA, but they differ from those of earlier reports showing the V 21D and V x editors to inhibit completely the binding of 56R to dsDNA (4,18,50). The basis for the difference is unclear.…”
Section: Igm Molecules Secreted By 56rv 21d-and 56rv X-expressing Hybsupporting
confidence: 40%
“…It is also curious that both N region diversity and somatic hypermutation often result in arginines encoded in CDR3. This raises the possibility that Igr could be selected to bind a particularly charged antigen moiety; paratopes with arginine have been implicated in anti-DNA-mediated autoimmunity [18]. Eleven arginine residues not encoded by V or J segments are found in just the 22 CDR3 reported here.…”
Section: Phylogenetic Analysesmentioning
confidence: 75%
“…B cell hybrids expressing VH56RϩV 38c IgM (hybridoma 160.3) and VH56RϩV 21D IgM (hybridoma 79.1) were derived from a VH56R mouse with graft-versus-host disease (15). In addition, we used VH56R/76RϩV 38c IgM and IgG hybridomas (30) and a VH56RϩV x IgM hybridoma (25). The hybridomas used in this study were analyzed by RT-PCR and ELISA to minimize the possibility of allelic and isotypic inclusion (15,25).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we used VH56R/76RϩV 38c IgM and IgG hybridomas (30) and a VH56RϩV x IgM hybridoma (25). The hybridomas used in this study were analyzed by RT-PCR and ELISA to minimize the possibility of allelic and isotypic inclusion (15,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation